Schweigen in Versen : Text, Übersetzung und Studien zu den Schweigegedichten Gregors von Nazianz (II,1,34A/B) - Kuhn, Thomas S. (Beiträge zur Altertumskunde, 2014)
The little-researched poetry of Gregory of Nazianzus reflects a remarkable interweaving of Judeo-Christian thought and the Greek-Pagan poetic tradition. This book includes a bilingual edition and analysis of the imagery in the double-poem 'On Silence During Lent' (Carm. II,1,34A/B), a work that offers an especially vivid illustration of the often innovative interposition of different traditions